From Röntgen rays to carbon ion therapy: the evolution of modern radiation oncology in Germany - Lischalk, Jonathan W; König, Laila; Repka, Michael C.; Uhl, Matthias; Dritschilo, Anatoly; Herfarth, Klaus; Debus, Jürgen (International journal of radiation oncology, biology, physics, 2016)
Beginning with the discovery of X rays in 1895, German scientists and clinicians were - instrumental in establishing the fields of diagnostic and therapeutic radiology, creating - the first radiation therapy peer-reviewed journal, and holding the first international - oncologic conference. These landmark achievements profoundly influenced the nascent - field of radiation oncology. However, the rapid early scientific progress was halted - by World War I, derailed during World War II, and slowly reestablished amid the divisions - of the Cold War.
Gesehen am 02.06.2020